Methylation metabolites in amniotic fluid depend on gestational age. (31st May 2013) - Imbard, Apolline; Blom, Henk J.; Schlemmer, Dimitri; Barto, Rob; Czerkiewicz, Isabelle; Rigal, Odile; Muller, Françoise; Benoist, Jean‐François
ABSTRACT Objective Methylation metabolism is essential for fetus development. However, normative data for amniotic fluid (AF) concentrations of methylation metabolites at different gestational ages are lacking. We aimed to determine in AF reference values of 14 intermediates involved in methylation. Methods Two hundred sixty‐eight AFs sampled between 14 and 39 weeks of gestation were retrospectively selected in our AF bank. Next, we measured methionine (Met)‐cycle intermediates [S‐adenosyl Met (AdoMet), S‐adenosyl‐l‐homocysteine (AdoHcy), total Hcy, Met, and methyl malonic acid] and methyl donors and methyl acceptors (betaine, dimethylglycine, sarcosine, free and total choline, free and total ethanolamine, creatine, and guanidinoacetate) by liquid chromatography coupled with tandem mass spectrometry. Results Reference ranges according to gestational age were determined for each parameter. Strong correlations between metabolites directly connected in their metabolic pathway and between total Hcy and betaine were observed. Conclusion Methionine, an essential amino acid required for protein synthesis, is the only parameter that dramatically decreases with gestational age. The AdoMet/AdoHcy ratio exponentially increases from 25 weeks of gestation, which could reflect increasing methylation capacities. The negative correlation between betaine and total Hcy together with a constant betaine to dimethylglycine ratio during gestation suggests that betaine may be used as a methyl donor during fetal life. © 2013 John Wiley & Sons, Ltd.